Role of community pharmacists in medication management during COVID-19 lockdown. (3rd April 2021) - Akour, Amal; Elayeh, Eman; Tubeileh, Razan; Hammad, Alaa; Ya'Acoub, Rawan; Al-Tammemi, Ala'a B.
ABSTRACT: Preventive and control measures implemented by many countries to mitigate the spread of COVID-19 may negatively impact medication and chronic disease management, which can interfere with achieving patients' therapeutic goals. This study aims to evaluate the effect of the COVID-19 lockdown on these aspects, while exploring the role of community pharmacists. A cross-sectional study was conducted via a web-based questionnaire that targeted individuals who suffer from chronic diseases in Jordan. Participants were recruited by convenience sampling and were asked to self-report their ability to access medication, and the perceived role of community pharmacists. Among the 431 participants, the mean age ± SD (years) was 53.8 ± 13.7 and 60.1% (n= 259) were females. Participants mainly reported difficulties in accessing medication (n=198, 45.9%), reduced supplies or unavailability of medications (n=213, 49.4%), nonadherence to medications due to lack of access (n=98, 22.7%) and high costs (n=85, 19.7%). Participants avoided follow-ups due to a fear of infection (n=367, 82.5%) or prolonged waiting time in clinics (n=322, 74.7%). An increased reliance on the community pharmacy for medical advice was reported by 39.9% (n=172) of the participants, with half of them (n=217, 50.3%) depending on the pharmacists for advice regarding over-the-counter medications and COVID-19-related information (n=119, 27.6%). There is an urgent need to involve community pharmacists in medication and chronic disease management with a focus on patient adherence to ensure the optimal management of such vulnerable patient groups. Future studies to assess the effect of pharmacists' contributions towards enhancing medication/disease management are warranted.